The Effect of Project-Based Learning with a STEM Approach on Students Creative Thinking Ability and Science Process Skills - Sidabutar, Tri Fitri Cahyati; Djulia, Ely; Sinaga, Marlina (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Creative thinking ability is one of the essential demands of 21st-century learning, which needs to be supported by science process skills to foster deeper understanding and meaningful learning experiences. However, science learning in schools is still largely dominated by lecture methods with minimal practical activities, resulting in students being less active, untrained in creative thinking, and rarely engaged in scientific processes. This study aims to investigate the effect of the Project-Based Learning (PjBL) model with a STEM (Science, Technology, Engineering, and Mathematics) approach on students’ creative thinking ability and science process skills in the topic of elements, compounds, and mixtures. The research employed a quasi-experimental method with a pretest-posttest control group design for creative thinking ability and a posttest-only control group design for science process skills. The sample consisted of two eighth-grade classes selected through random sampling, with 30 students in each class. One class was assigned as the experimental group, taught using the STEM-based PjBL model, while the other served as the control group using conventional instruction. Research instruments included essay tests and observation sheets. Data analysis using the t-test revealed a significant effect on creative thinking ability (p = 0.001, p < 0.05) and science process skills (p = 0.004, p < 0.05). The novelty of this study lies in the integration between the design of PjBL and the STEM approach, with systematic measurement of two important indicators of 21st-century learning: creative thinking and science process skills, in the context of applied basic chemistry topics. Thus, the findings affirm that integrating PjBL with STEM is effective in fostering 21st-century skills. Based on these results, it is recommended that innovative and contextually relevant projects be designed to support the development of meaningful science learning.